The canine hookworm genome: analysis and classification of Ancylostoma caninum survey sequences - Abubucker, Sahar (2007)
Hookworms infect nearly a billion people. The Ancylostoma caninum hookworm of canids is a model for studying human infections and information from its genome coupled with functional genomics and proteomics can accelerate progress towards hookworm control. As a step towards a full-scale A. caninum genome project, we generated 104,000 genome survey sequences (GSSs) and determined the genome size of the canine hookworm. GSSs assembled into 57.6 Mb of unique sequence from a genome that we estimate by flow cytometry of isolated nuclei to be 347±1.2 Mb, substantially larger than other Rhabditina species. Gene finding identified 5,538 genes in the GSS assembly, for a total of 9,113 non-redundant A. caninum genes when EST sequences are also considered. Functional classifications of many of the 70% of genes with homology to genes in other species are provided based on Gene Ontology and KEGG associations and secreted and membrane-bound proteins are also identified.